Quality assessment of student housing facilities through post-occupancy evaluation. (2nd September 2016) - Sanni-Anibire, Muizz O.; Hassanain, Mohammad A.
ABSTRACT: This research employs the use of post-occupancy evaluation (POE) to assess the quality of an existing conglomerate of student housing facilities in a university campus in Saudi Arabia. The assessment methods used include walkthroughs, questionnaire surveys and focus group meetings. The key performance issues identified include the performance and control of thermostats, quality of building support services, size of rooms, furniture and proximity to the cafeteria. Quality score calculations showed that the design quality and indoor environmental quality were moderate, while building support services was of low quality. This study provides recommendations to serve as feedback, and feed forward, to improve the design and management of student housing facilities. Thus the research has practical value to potential stakeholders in the design, construction and management of these facilities.